2020
DOI: 10.1002/alr.22660
|View full text |Cite
|
Sign up to set email alerts
|

Association of spontaneous cerebrospinal fluid rhinorrhea with transverse venous sinus stenosis: a retrospective matched case‐control study

Abstract: Background A significant proportion of spontaneous cerebrospinal fluid sCSF leaks are associated with idiopathic intracranial hypertension IIH The aim of this study was to assess the association between sCSF rhinorrhea and transverse venous sinus stenosis VSS a feature commonly observed in IIH with a proposed role in its pathophysiology Methods In this single-center retrospective matched case-control study venous and pituitary imaging data of consecutive patients undergoing endoscopic surgery for sCSF rhinorrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
18
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 37 publications
3
18
2
Order By: Relevance
“…In their study, Bedarida et al found higher rates of TSS in the patient group with sCSF rhinorrhea ( p < 0.001). They interpreted that their results and those of a previous study favor the association between sCSF leaks and idiopathic intracranial hypertension (IIH) 1 . Moreover, they proposed that the main pathophysiologic hypothesis of sCSF leaks may be explained as being secondary to IIH 1 .…”
mentioning
confidence: 65%
See 3 more Smart Citations
“…In their study, Bedarida et al found higher rates of TSS in the patient group with sCSF rhinorrhea ( p < 0.001). They interpreted that their results and those of a previous study favor the association between sCSF leaks and idiopathic intracranial hypertension (IIH) 1 . Moreover, they proposed that the main pathophysiologic hypothesis of sCSF leaks may be explained as being secondary to IIH 1 .…”
mentioning
confidence: 65%
“…Association of spontaneous cerebrospinal fluid rhinorrhea with transverse venous sinus stenosis a retrospective matched case-control study I read with great interest the article by Bedarida et al, 1 in which they investigated the presence of transverse venous sinus stenosis (TSS) in the patient group undergoing endoscopic surgery for spontaneous cerebrospinal fluid (sCSF) rhinorrhea. I sincerely thank the authors for conducting such original research and including a considerable number of patients.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We have read with great interest Dr Onder's correspondence 1 regarding our article 2 . In our study, we reported a higher incidence of transverse venous sinus stenosis (TSS) in a group of patients operated on for a spontaneous cerebrospinal fluid (sCSF) leak than in a control group of patients adjusted for age and sex.…”
mentioning
confidence: 81%